2017
DOI: 10.1136/bmjopen-2016-014719
|View full text |Cite
|
Sign up to set email alerts
|

Do patients and health care providers have discordant preferences about which aspects of treatments matter most? Evidence from a systematic review of discrete choice experiments

Abstract: ObjectivesTo review studies eliciting patient and healthcare provider preferences for healthcare interventions using discrete choice experiments (DCEs) to (1) review the methodology to evaluate similarities, differences, rigour of designs and whether comparisons are made at the aggregate level or account for individual heterogeneity; and (2) quantify the extent to which they demonstrate concordance of patient and healthcare provider preferences.MethodsA systematic review searching Medline, EMBASE, Econlit, Psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 66 publications
(123 reference statements)
4
63
0
Order By: Relevance
“…Instead of testing the alignment of patient/physician pairs, in this study patients and physicians responded independent from each other and concordance was assessed in terms of the RI of specific treatment attributes. While paired comparisons are an interesting methodological approach, the majority of studies analyzing the concordance of patient and physician preferences still rely on DCEs ( M. Harrison, Milbers, Hudson, & Bansback, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Instead of testing the alignment of patient/physician pairs, in this study patients and physicians responded independent from each other and concordance was assessed in terms of the RI of specific treatment attributes. While paired comparisons are an interesting methodological approach, the majority of studies analyzing the concordance of patient and physician preferences still rely on DCEs ( M. Harrison, Milbers, Hudson, & Bansback, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…They may include even non-health outcomes of health interventions [ 35 ]. Interestingly, patient preferences can differ compared to physicians’ judgment, as shown in different systematic reviews [ 36 , 37 ]. Most studies revealed a disparity between the preferences of actual patients and those of physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of testing the alignment of patient/physician pairs, in this study patients and physicians responded independently from each other and concordance was assessed in terms of the relative importance of specific treatment attributes. While paired comparisons are an interesting methodological approach, the majority of studies analysing the concordance of patient and physician preferences still rely on separate sample DCEs [ 37 ]. However, a recent Japanese study explicitly evaluated treatment goal alignment between psoriasis patients and their paired physicians.…”
Section: Discussionmentioning
confidence: 99%